2015
DOI: 10.1111/bph.13112
|View full text |Cite
|
Sign up to set email alerts
|

BJP is linking its articles to the IUPHAR/BPS Guide to PHARMACOLOGY

Abstract: Linked EditorialsThis Editorial is part of a series. To view the other Editorials in this series, visit: http://onlinelibrary.wiley.com/doi/10.1111/bph.12956/abstract; http://onlinelibrary.wiley.com/doi/10.1111/bph.12954/abstract; http://onlinelibrary.wiley.com/doi/10.1111/bph.12955/abstract and http://onlinelibrary.wiley.com/doi/10.1111/bph.12856/abstract.VideoTo view the video on the IUPHAR/BPS Guide to PHARMACOLOGY, visit: https://www.youtube.com/watch?v=Qhy3q33VtRI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…This includes details on PubMed ID statistics in curated GtoPdb content. The same post also shows how engagement with British Journal of Pharmacology (BJP) has extended the previous provision of live out-links ( 50 ), to now include in line links, rather than the previous method of adding separate tables to manuscripts.…”
Section: Collaborations Connectivity and Interoperabilitymentioning
confidence: 92%
“…This includes details on PubMed ID statistics in curated GtoPdb content. The same post also shows how engagement with British Journal of Pharmacology (BJP) has extended the previous provision of live out-links ( 50 ), to now include in line links, rather than the previous method of adding separate tables to manuscripts.…”
Section: Collaborations Connectivity and Interoperabilitymentioning
confidence: 92%
“…To achieve this, the GtoPdb team and the CGTP editors collaborate with the Wiley publishers on what is, in effect, the automatic converting of (pre-tagged) sections of the database directly into the online CGTP PDF documents. The second initiative, also a collaboration with the BJP, involves marking-up tables of links (ToLs) for both regular papers and reviews ( 32 ). An example is a recent invited review on epigenetic pathway targets for the treatment of disease, which can be viewed at http://onlinelibrary.wiley.com/doi/10.1111/bph.12848/epdf (the ToLs are on the second page) ( 33 ).…”
Section: Connectivity Collaborationsmentioning
confidence: 99%
“…The invited review provided the curatorial starting point for the capture of new ligands and targets to populate the database and these were consequently surfaced as ToLs in the article. The third journal-to-database initiative is a logical extension of the previous two ( 32 ). This involves an updated version of the BJP instructions-to-authors that now includes recommendations on resolving the molecular identities of targets and ligands at the submission stage.…”
Section: Connectivity Collaborationsmentioning
confidence: 99%
“…HO-1 is an antioxidative and cytoprotective enzyme, which degrades haem to biliverdin, iron ions and carbon monoxide (Maines, 1997). Previous studies indicated that overexpression of HO-1 reduced DGCR8 dimer formation and expression of DGCR8, which is a protein involved in miRNA processing and requires F I G U R E 7 Treatment with 1m-6 attenuates lipid accumulation and plaque formation in atherosclerosis-prone mice.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were designed to generate groups of equal size, using randomization and blinded analysis. Group sizes in each protocol were determined based on our previous studies, preliminary results and the power analysis (McGrath, Pawson, Sharman, & Alexander, 2015). All the data, including outliers, were included in data analysis and presentation.…”
Section: Methodsmentioning
confidence: 99%